A green new deal after Corona: What we can learn from the financial crisis - Mats Kröger; Sun Xi; Olga Chiappinelli; Marius Clemens; Nils May; Karsten Neuhoff; Jörn Richstein (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Already after the financial crisis in 2008/2009 there was a debate on whether elements aiming at sustainable development can be part of the stimulus packages and support the recovery of the economy. Despite the instinct of policy makers to prioritise battle-tested policies during a crisis, significant levels and different types of climate-friendly components were integrated in the 2009 stimulus packages across the globe. The experience from the past crisis proves that such climate-oriented economic stimulus policies not only raise investments with benefits for economic output and jobs in the near term, but can also lay the groundwork for long-term innovation and economic development aligned with environmental constraints. By introducing policies such as Contracts for Difference for low-carbon industrial processes and renewable energy, and Green Public Procurement, governments can further ensure that their stimulus packages are transformative. Hence, "green stimuli" have the capacity to boost economic recovery also during the current Corona crisis.
Keywords: 330